The function of dramatic dialogue in stereoscopic the content of Kurdish “Hayranok - Simo, Ibrahim Ahmed; Meeqdad, Maknon Muhammed Tahir (Journal of Duhok University, 2019)
This paper is about (The function of dramatic dialogue in stereoscopic the content of Kurdish “Hayranok”). In this paper, at the beginning I enlighten the term dialogue, then after I research many definitions, I explain and clarify dialogue. After that, I speak about the function of dramatic dialogue where I refer to opinions and thoughts of many experts and scholars regarding functions of dramatic dialogue as each one of them explain the functions according to their own understandings. Once I collect and study all these different explanations, I identify the functions of dramatic dialogue in many points.Then with examples, I implement the practical functions of dramatic dialogues in Kurdish “Hayranok” point by point.In the conclusion, it becomes clear to me that dialogue in Kurdish “Hayranok” fulfills all functions of dramatic dialogues very clearly and very well.